2018
DOI: 10.21272/mmi.2018.2-30
|View full text |Cite
|
Sign up to set email alerts
|

Student as stakeholder: “voice of customer” in higher education quality development

Abstract: STUDENT AS STAKEHOLDER: "VOICE OF CUSTOMER" IN HIGHER EDUCATION QUALITY DEVELOPMENTAccording to the continuous improvement principles, all Higher Education Institutions (hereafter -HEIs) focus on the requirement to improve organizational processes and achieve quality, create added value and achieve stakeholders' satisfaction. The aim of the research is to analyse the concept "quality in higher education", define the stakeholders within the system of higher education and to analyse students' opinion about the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
(33 reference statements)
0
30
0
3
Order By: Relevance
“…The literature review indicated some of the activities a university may consider for organisational sustainability: identify quality and sustainability leaders at all university levels (Marshall et al , 2017); ensure higher management support (Tuominen, 2011a, 2011b; Ozoliņš et al , 2018); ensure personnel awareness about sustainability activities (Tuominen, 2011a, 2011b); focus on stakeholders needs (Zink, 2007; Lapiņa et al , 2015; Marshall et al , 2017; Degtjarjova et al , 2018); ensure comprehension of the main sustainability elements (Tuominen, 2011a, 2011b; Ņikitina and Lapiņa, 2017); integrate sustainability in the university’s strategy (Mežinska et al , 2015; Zeps and Ribickis, 2016; Cazeri et al , 2018); develop a CSR strategy (Cazeri et al , 2018); identify and measure sustainability KPIs (Radoslav and Jankalova, 2016; Medne and Lapiņa, 2019); analyse KPIs results and compile an improvement plan (Tuominen, 2011a, 2011b; Iljins et al , 2017); and benchmark sustainability best practices (Dupada et al , 2013). …”
Section: Sustainability and Development Of Quality System In Higher Education Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review indicated some of the activities a university may consider for organisational sustainability: identify quality and sustainability leaders at all university levels (Marshall et al , 2017); ensure higher management support (Tuominen, 2011a, 2011b; Ozoliņš et al , 2018); ensure personnel awareness about sustainability activities (Tuominen, 2011a, 2011b); focus on stakeholders needs (Zink, 2007; Lapiņa et al , 2015; Marshall et al , 2017; Degtjarjova et al , 2018); ensure comprehension of the main sustainability elements (Tuominen, 2011a, 2011b; Ņikitina and Lapiņa, 2017); integrate sustainability in the university’s strategy (Mežinska et al , 2015; Zeps and Ribickis, 2016; Cazeri et al , 2018); develop a CSR strategy (Cazeri et al , 2018); identify and measure sustainability KPIs (Radoslav and Jankalova, 2016; Medne and Lapiņa, 2019); analyse KPIs results and compile an improvement plan (Tuominen, 2011a, 2011b; Iljins et al , 2017); and benchmark sustainability best practices (Dupada et al , 2013). …”
Section: Sustainability and Development Of Quality System In Higher Education Contextmentioning
confidence: 99%
“…ensure personnel awareness about sustainability activities (Tuominen, 2011a, 2011b); focus on stakeholders needs (Zink, 2007; Lapiņa et al , 2015; Marshall et al , 2017; Degtjarjova et al , 2018);…”
Section: Sustainability and Development Of Quality System In Higher Education Contextmentioning
confidence: 99%
“…The results of a study on the history of development in European and American countries published by (Du et al, 2017) have shown that improving the level of higher education can strengthen the capacity of talents to shape national economies, and can also promote prosperity and social progress. Degtjarjova et al (2018) indicate two main strategies for defining the quality of education in universities. The first one is process-oriented, the so-called IPO model, which includes elements of Input -Process -Output.…”
Section: Quality Of Process Educationmentioning
confidence: 99%
“…http://creativecommons.org/licenses/by-nc-sa/3.0/deed.es_ES y Fossatti, 2017; Choudhary y Paharia, 2018), que se caracterizan por un rápido crecimiento de las instituciones participantes y de la respectiva matrícula (Jain, Sahney y Sinha, 2013;Ganga-Contreras, et al, 2019), por la aparición de nuevos tipos de instituciones (Yilmaz, 2019), incrementos en las restricciones presupuestarias (Martínez-Argüelles, Blanco y Castán, 2013), cambios en las regulaciones (Sultan y Wong, 2014), los mayores niveles de demanda por control de calidad (Brunner y Uribe, 2007), el desarrollo de un mercado de educación global (Abdullah, 2006), y por la dificultad de las instituciones para mantener sus ventajas competitivas (Cubillo-Pinilla, et al, 2009). Dado lo anterior, las instituciones de educación superior tienen el desafío de adaptarse a los cambios del entorno (Thieme, Araya-Castillo y Olavarrieta, 2012;Ganga, et al, 2019;Tamutienė y Matkevičienė, 2019), reexaminar sus estructuras, estrategias y procesos (Araya-Castillo, et al, 2018), adoptar estrategias competitivas que permitan diferenciar sus ofertas (DeShields, Kara y Kaynak, 2005;Brunner y Ganga, 2016), enfocar sus esfuerzos en las actividades de comercialización (Ivy, 2008), y desarrollar una base sólida que les permita alcanzar altos niveles de calidad (Hota y Sarangi, 2019) a través de la creación de valor y la mejora continua de sus procesos organizacionales (Degtjarjova, Lapina y Freidenfelds, 2018).…”
Section: Introductionunclassified